Recruitment and Selection of Human Resources in Industry 4.0 Era: New Model Conceptual - Ponamon, Jolie Febri; Rumagit, Selvi; Sumual, Tinneke E. M.; Sumual, Shelty D.M. (JR Education, 2023)
This research aims to develop a new conceptual model in the recruitment and selection process for human resources (HR) in the Industry 4.0 era. Rapid changes in technology, digitalization, and automation in the context of Industry 4.0 pose new challenges in the recruitment and selection of a workforce that is relevant, adaptive, and has appropriate competencies. This research method will use qualitative and quantitative approaches. Qualitative data will be obtained through in-depth interviews with industry practitioners, human resource managers, and Industry 4.0 experts. Meanwhile, quantitative data will be obtained through a survey that assesses the key competencies needed by workers in the Industry 4.0 era. In the analysis stage, this research will use thematic analysis for qualitative data and statistical techniques for quantitative data. The results of the analysis will be used to develop a new conceptual model that includes key dimensions such as digital skills, creativity, adaptation skills, and collaboration. This research is expected to make a significant contribution to understanding how HR recruitment and selection can be adapted to the demands of Industry 4.0. It is hoped that the resulting conceptual model can become the basis for organizations and educational institutions to improve the effectiveness of recruitment and selection processes, ensuring that the resulting workforce can adapt successfully in an ever-changing work environment.